Volumetric Change Calculation for a Landfill Stockpile Using UAV Photogrammetry - Kaamin, Masiri (International Journal of Integrated Engineering, 2019)
A growth in population and urbanization is the major factor of accretion in municipal solid waste (MSW) generation in Malaysia. The higher percentage of MSW particularly in Peninsular Malaysia, a quantity of 16,200 tons per day in 2001 increase to 19,100 tons per day in 2005 which make an average of 0.8 kg/capita/day. The amount continues expanding yearly and approximately 8 million tons per day especially in urban areas. Hence, the landfill management has to design a landfill using basic design parameters method which use past record to complement with the correlation factor during the situation. However, this method will exert more time before producing the result. This research aims to consider the calculation of volumetric change calculation for a landfill stockpile using Unmanned Aerial Vehicle (UAV) photogrammetry and predict the targeted life span as an alternative method. The case study is located at Rimba Mas, Mukim Titi Tinggi, Perlis. The process involved throughout this study are planning and preparation before the flight, data collection using UAV, image processing and analyzing data from the image. This study focusses more on the method to calculate the volume using UAV photogrammetry and generate the data into Pix4dmapper. This observation took 2 months periodically to oversee the changes in volume at the landfill site. The result of analysis showed that, there were differences and increasing in the volume of waste for each months. The volume information obtained from UAV photogrammetry and the Pix4dmapper software can help in future for better plan in managing the landfill and MSW.